How Do Electric Fields Coordinate Neuronal Migration and Maturation in the Developing Cortex? - Medvedeva, Vera P.; Pierani, Alessandra (Frontiers in Cell and Developmental Biology, 2020)
During development the vast majority of cells that will later compose the mature cerebral cortex undergo extensive migration to reach their final position. In addition to respond to intrinsically distinct migratory behaviors, cells encounter vastly different microenvironments. These range from axonal tracts to cell-dense matrices, electrically active regions and extracellular matrix components, which may all change overtime. Furthermore, migrating neurons themselves not only adapt to their microenvironment but also modify the local niche through cell-cell contacts, secreted factors and ions. In the radial dimension, the developing cortex is roughly divided into dense progenitor and cortical plate territories, and a less crowded intermediate zone. The cortical plate is bordered by the subplate and the marginal zone which are populated by neurons with high electrical activity and characterized by sophisticated neuritic ramifications. Neuronal migration is influenced by these boundaries resulting in dramatic changes in migratory behaviors as well as morphology and electrical activity. Modifications in the levels of any of these parameters can lead to alterations and even arrest of migration. Recent work underlies that morphology and electrical activity of migrating neuron are interconnected and the aim of this review is to explore the extent of this connection. We will discuss on one hand how the response of migrating neurons is altered upon modification of electrical properties intrinsically and whether, on the other hand, electric properties of the cellular environment can modify the morphology and electrical activity of migrating cortical neurons.